TINJAUAN YURIDIS ASAS PERADILAN SEDERHANA CEPAT DAN BIAYA RINGAN TERHADAP PUTUSAN EKONOMI SYARIAH PENGADILAN AGAMA KOTA MALANG TAHUN 2019 - Umi Nur Kholifah; Andi Ardiyan Mustakim; Fitriyah, Faridatul (Qawanin: Jurnal of Economic Syaria Law, 2022)
The existence of contract furtherly sharia economic contract can’t avoid from dispute’s risk. According of Act Number 3 of 2006 about Islamic Court, legal dispute resolution of sharia economic dispute is being Islamic Court’s authority. One of Islamic Court in Indonesia is Malang City Islamic Court which is must obey the principle of simple justice, quick, and low cost including SEMA Number 3 of 2014. From the beginning of observation, Malang City Islamic Court disobeying the principle of simple justice, quick, and low cost which implemented in SEMA Number 3 of 2014. The focus of this research is (1) what is the concept of the principle of simple justice, quick, and low cost in Indonesian’s act? And (2) what is legal view of the principle of simple justice, quick, and low cost about sharia economic verdict at Malang City Islamic Court in 2019? This research using library research and statue approach, also using legal material in the form of primary legal material, secondary legal material, and tertiary legal material for the example books, journals, acts, legal dictionary, etc. And then all of those legal material will be adjusted within the object of this research. The result of this research is the concept of the principle of simple justice, quick, and low cost can called principle is just because fulfill the meaning of legal principle and the function of legal principle. The principle of simple justice, quick, and low cost have been implemented in various judicial procedural law at Indonesia. Sharia economic verdict at Malang City Islamic Court in 2019 from legal view still can’t obey the principle of simple justice, quick, and low cost and also SEMA number 2 of 2014.